Konseptualisasi Peran Kepala Sekolah sebagai Agen Perubahan di Era Disrupsi Digital: Systematic Literature Review (SLR) dengan Pendekatan PRISMA - Aisyah Putri Zahrani; Hery Setiyatna (JoEMS (Journal of Education and Management Studies), 2026)
Purpose: The purpose of this study is to summarize the best practices of adaptive leadership that are in line with technological advances, shifts in learning systems, and the dynamics of current school/madrasah governance Methodology/approach: This study examines various empirical and conceptual literature sources published over the past five years. It uses a systematic approach, examining more than 30 nationally indexed articles to enrich the discussion Findings: Based on the results of the study, it was revealed that adaptive leadership strategies will be optimal if they emphasize the combination of technology and pedagogy, continuous improvement of the quality of human resources from teachers, staff, and students, flexibility in managing change, the formation of an innovative and mutually supportive school environment/culture, and the existence of monitoring and evaluation of implementation carried out by utilizing digital media Practical implications: Schools and Islamic schools are required to build innovative learning environments by providing digital-based platforms for both learning media and school administration systems. Furthermore, institutions must actively develop human resources willing to develop. This begins with principals, who must adapt to digital disruption, and teachers and staff, who must receive intensive training in technology use for implementation in daily teaching and learning activities. Originality/value: The novelty of this study provides a new theoretical contribution by shifting the conventional paradigm; principals in the era of disruption do not only act as facilitators of digital tools, but must also be able to implement dynamic data-driven decision-making to monitor the progress of educators and students.